Lycopodium clavatum e Phosphorus modulam a resposta de citocinas, protegem neurônios mientéricos e diminuiem a inflamação em ratos Wistar infectados pelo T. cruzi - Brustolin, Camila Fernanda (2014)
To evaluate the influence of treatment with highly diluted Lycopodium clavatum or Phosphorus solutions on parasitological, inflammatory, immunological, number and morphology of myenteric neurons features in Wistar rats infected by T. cruzi. The experiment was conducted as a blind, controlled, randomized by lottery assay. The study involved 75 male rats (Rattus norvegicus, Wistar lineage), 45 days old, intraperitoneally inoculated with 5x106T. cruzi Y strain blood trypomastigotes and divided into three groups: IC (infected control group, treated with 7% hydroalcoholic solution), Ly (treated with Lycopodium clavatum 13CH - 1:1026 dilution), Phos (treated with Phosphorus 13 CH - 1:1026 dilution). All treatments were offered ad libitum on the second day before the infection, and on the second, fifth and seventh day after infection (dai), provided for 16 consecutive hours. Evaluated parameters: pre-patent period, parasitemia peak, total parasitemia, quantification and morphometry of myenteric neurons, inflammatory infiltrate (HE) and cytokines (IL-1 alpha and beta, IL2, IL4, IL6, IL10, IL12, IFN-gamma, TNF-alpha, GM-CSF - Multiplex Invitrogen). No significant difference was observed for any parasitological parameter evaluated. The neuronal quantification of Ly and Phos groups on 322nd dai showed, respectively, 76.2% and 75.4% protection (p<0.01) to distal colon neurons compared to IC group. The morphometric analysis showed that on 125th dai in both proximal and distal segments, Ly and Phos promoted neuronal body hypertrophy compared to IC group (p<0.0001).On 322nd dai Ly group presented neuronal hypertrophy in proximal colon in relation to IC (17.1%) and Phos (40.3%) groups (p <0.0001).In the distal colon, Phos group presented significantly smaller neurons (p <0.0001) than IC (21.2%) and Ly (20.0%) groups.When analyzing the infection evolution (125dai x 322dai) it was observed in the proximal colon, that IC and Ly groups showed 86.8% and 18.9% neuronal hypertrophy (p<0.0001), respectively.Increase related to cytoplasmic area hypertrophy, followed by a nuclear area increase.The Phos group showed neuronal hypotrophy (28.8%), and the reduction was mainly due to cytoplasmic area decrease (45.9%), while the nuclear area increased by 3%.In distal colon neuronal hypertrophy (p <0.0001) was observed in all groups analyzed. In the heart, on 10th dai animals treated with Ly (45%) and Phos (52.5%) showed less inflammation when compared to IC (p<0.01). In the liver, on several dai (5th, 10th and 24th), the number of inflammatory foci was lower in animals treated with Ly (42.8%) and Phos (37.3%) (p <0.01). In the intestine on 10th day of infection, animals treated with Ly demonstrated a reduction in inflammation of 51.8% and 67.5%, when compared to IC and Phos groups, respectively. On 24th dai both Ly (29.7%) and Phos (40.5%) treatments presented less inflammation than IC (p<0.01). In striated skeletal muscle, on 24th dai, Phos animals showed the number of inflammatory foci 43.6% higher than IC (p=0.0192). About cytokine dosage, it was observed an increase on concentration of GM-CSF on 5th dai, IL4 and IFN-γ on 10th dai and IL1-β, IL6 and IL12 on 24th dai, as well as decrease of TNF-α after treatment, IL1-α and IL1-β on 10th dai and IL10 on 24th dai for animals treated with Lycopodium clavatum homeopathic medicine. In Phosphorus group, increased concentrations of IL2, IL4, IL10, IL12, TNF-α and IFN-γ on 5th dai, and a reduction of IL1-α and IL4 on 10th dai and IL1-α and IL2, IL4 and IL12 on 24th dai. Strong partial correlation was observed on the three evaluated groups (IC, Ly and Phos) between number of distal colon neurons 322 dai and IFN-γ and TNF-α (p<0.009/ r>0.7) cytokine. The homeopathic treatment with Lycopodium clavatum or Phosphorus medicines (13CH potency - 1:1026 dilution) promoted, in a different way, beneficial effects on several parameters evaluated in T. cruzi infection in Wistar rats. The treated groups establish balance of host-parasite relation differently, with lower cell and tissue damage to the infected host. Lycopodium clavatum medicine modifies the animals immune response form, promoting less inflammation and protecting the intestine, preserving the myenteric neuronal population and promoting hypertrophy of neurons. Phosphorus medicine reduces cardiac tissue inflammation and protects neurons less sharply. The evaluation of several immune response markers at the process different times eases the control of this process understanding, either by natural means of maintaining organism homeostasis (infected control) or by intervention with medicines. Highly diluted medicines provide benefits in the treatment of experimental infection by T. cruzi, strengthening the importance of deepening these studies to propose new therapeutic approaches for this infection and infectious diseases in general.